Herbicide Use Strategy and Its Economy as a Weed Management Option in Wheat Varieties (Bangladesh Agronomy Journal, 2021)
Weed pressure is an additional threat to high temperature stressed wheat crop for its optimum production. A field experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during Rabi 2017-2018 to assess the response of wheat varieties to different weed managements and its economical viability. As such three varieties i.e. BARI Gom-28, BARI Gom-29, and BARI Gom-30 along with five weed managements viz. control (no weeding), two hand weeding at 20 and 40 DAS, Panida 33EC (Pendimethalin) @ 2000 ml ha-1 spray at 5 DAS as pre-emergence, Affinity 50.75 WP (Isoproturon) @ 1500 g ha-1 spray at 25 DAS as post-emergence and Panida 33EC (Pendimethalin) @ 2000 ml ha-1 at 5 DAS + Affinity 50.75 WP (Isoproturon) @ 1500 g ha-1 at 5 & 25 DAS were treatment variables tested under split plot design.Cynodon dactylon, Cyperus rotundus, Echinochloa colona, Eleusine indica, Chenopodium album, Alternanthera philoxeroides, Brassica kaber, Leliotropium indicum, Vicia sativa,etc.werethe major weeds as determined based on their field intensity.Results revealed that BARI Gom-30 out-yielded other varieties with the highest grain yield (3.01 t ha-1). Pre-emergence application of Panida 33EC at 5 DAS proved as suitable weed management compared to other methods. BARI Gom-30 in combination with Panida 33EC @ 2000 ml ha-1 spray at 5 DAS as pre-emergence gave higher yield and yield attributes while BARI Gom-28 under no weeding check showed lower grain yield (2.09 t ha-1). Economically maximum gross return (Tk.75761.52ha-1),net income (Tk.21775.92ha-1), and BCR (1.41) were associated with Panida 33EC treatment when minimum values were obtained in the control plot (no weeding). So, the application of pre-emergence herbicide, Panida 33EC might be economically viable weed management ensuring a higher yield in wheat cultivation.Bangladesh Agron. J. 2020, 23(2): 119-125